ANALYSIS SEMIOTIC IN SHERLOCK HOLMES FILM BY GUY RITCHIE - Lamusu, Agus Salim (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2024)
Semiotic Analysis in Sherlock Holmes Film By Guy Ritchie .In this research, the researcher looks for meanings and symbols that appear in the film Sherlock Holmes by Guy Ritchie which has a close relationship with the Illuminati association. The method used by the researcher in his research is the semiotic method of Ferdinand de Saussure which has two factors in determining the meaning of a symbol, namely the signifier and the signified. The results of this study show and explain what symbols appear and what the meanings of these symbols are that are closely related to the Illuminati, which appear in the film Sherlock Holmes by Guy Ritchie where researchers find several symbols that clearly have a close relationship with the Illuminati in the form of the symbols that appear and the meanings contained in these symbols.